Ratio Decidendi in the Enforcement if Mortgage Rights: Analysis of Surabaya District Court Decision No. 36/PDT.G/2023/PN SBY - Muhammad Fatih; Herdy Pratam Susantyo (Journal of Creative Power and Ambition (JCPA), 2026)
This study analyzes the ratio decidendi in Surabaya District Court Decision No. 36/Pdt.G/2023/PN Sby and identifies gaps in legal protection in the enforcement of Mortgage Rights. It employs normative juridical legal research using statutory, case, and conceptual approaches. Legal materials are analyzed qualitatively, systematically, and prescriptively through factual reconstruction, identification of the ratio decidendi, assessment based on theories of justice and Mortgage Rights, and mapping of the Judicial Protection Gap. The findings show that the Panel of Judges recognized the validity of the credit agreement and the Mortgage Right but considered that the debtor's payment delay could not be fully attributed to the debtor because of the impact of the COVID-19 pandemic. Restructuring was positioned as a mechanism that should be assessed before the auction continued; consequently, the court postponed enforcement and directed the parties to renegotiate. Although oriented toward substantive justice, the decision does not provide adequate parameters regarding proof of force majeure, the scope of restructuring obligations, the duration of postponement, interest and penalties, maintenance of the collateral, the status of the security right, renewal of auction documents, or the conditions for renewed enforcement. This study proposes a conditional-postponement model that preserves the Mortgage Right while requiring a measurable restructuring process, explicit risk allocation, and clear conditions for ending the postponement. The study contributes by integrating ratio decidendi analysis with the Judicial Protection Gap framework to assess both the quality and enforceability of judicial protection.